The influence of nature school’s curriculum on student’s environmentally caring behaviour (Study on Sekolah Alam Bekasi) - Setiani, Dewi; Putri, Raisa Widya (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: Character education aims to teach the traits needed to build good character, including moral awareness and action. The purpose of developing environmental awareness is to create harmony between humans and the environment, forming individuals who act to protect and utilize natural resources wisely. Nature schools, or Sekolah Alam, utilize the natural environment as a central component of their educational approach, blending formal academic content with outdoor experiential learning. The curriculum in this school focuses on character development, environmental awareness, and practical life skills, rather than traditional academic achievements. Method: In this research, observations were made of the effect of a nature-based curriculum on the awareness of the natural environment by students who attend nature schools, especially at Sekolah Alam Bekasi (SASI). This research uses a qualitative approach that goes through a systematic literature review to assess how the curriculum encourages environmental awareness among students. The data in this research was collected from social media observations, related journals, and publications of Sekolah Alam Bekasi (SASI). Findings: Key elements of the curriculum in Sekolah Alam Bekasi (SASI) include activities like waste management, sustainable farming, and the integration of religious principles with environmental education. The results show that the nature-based curriculum, which integrates environmental education with traditional academic subjects, significantly increases environmental awareness and behavior by students. Results indicate that the nature school curriculum significantly influences students' attitudes toward the environment by promoting practical engagement and ethical stewardship. Conclusion: This research emphasizes the importance of early environmental education in shaping individuals who are responsible and concerned about the environment. Novelty/Originality: This research exploration of how a nature-based curriculum, uniquely integrating environmental education, religious principles, and practical activities, fosters significant environmental awareness and ethical behavior among students at Sekolah Alam Bekasi (SASI).